PENGEMBANGAN DIRI SISWA BIDANG SENI RUPA DI SMP NEGERI 10 PADANG - Silvia Aryulanda, Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this researchis to showsthe process of Self-Development on study Fine Art, along with leader’s contribution and factors that give effect to the process of Self-Development on SMP Negeri 10 Padang. Type of research is qualitative descriptive, data collection techniques are conducted by observation, interviews and documentations. Data analysis by reducing, exposing, and verificationthen checking the legitimation data. The result of this research shows process of Self-Development have successed to found their soul, leader has evaluated their painting then give somepraises and motivating to increase their enthusiasm toward art for making class is condusive. factors impair the processing such as no funded for this activity and practice timeisn’t enough.Keywords: Self-Development, Fine Art, Activity Processed, Leader’s Contribution